Polycyclic aromatic hydrocarbons in the atmosphere and soils of Dalian, China: Source, urban-rural gradient, and air-soil exchange. (April 2020) - Wang, Yan; Bao, Meijun; Zhang, Yuwei; Tan, Feng; Zhao, Hongxia; Zhang, Qiaonan; Li, Qilu
Abstract: We investigated the concentrations, distributions, and sources of PAHs in the air and soils of Dalian, China, as well as their air-soil exchange trends. Total concentrations of PAHs in the air ranged from 6.37 to 124 ng/m 3 with an average of 23.1 ± 26.6 ng/m 3, while Σ15 PAHs in the soils ranged from 42.8 to 28600 ng/g with an average of 2580 ± 5730 ng/g. Significant spatial distribution of PAHs was discovered in the soils with a clear urban-suburban-rural decreasing gradient, suggesting urban area is more contaminated by PAHs due to frequent and intensive human activities. However, high PAH concentrations were also discovered in the air from several rural sites, implying some PAH sources have shifted from urban to suburban or rural areas. Source apportionment indicated that major sources of PAHs in the urban and suburban soils were traffic emission/oil spill and coal combustion respectively, whereas major sources in the rural soils were diverse. Air-soil partitioning result suggested that 3-ring PAHs were mostly volatilized from soil, 6-ring PAHs were deposited into soil, while the trends of 4∼5-ring PAHs varied with sampling site. Fluoranthene, Pyrene, and Chrysene were mostly discovered to be volatilized in the urban and suburban areas, but equilibrium or deposited in the rural area, indicating a potential urban-to-rural transport of PAHs. The atmospheric transport and source shift of PAHs from urban to rural areas highlighted the importance of PAH source control on a regional scale. Graphical abstract: Image 1 Highlights: An obvious urban-to-rural decreasing gradient of PAHs was discovered in the soils. High PAH levels in some rural air suggested an urban-to-rural shift of PAH source. Traffic emission/oil spill is the major PAH source in the urban area of Dalian. 4-ring PAHs were mainly volatilized in urban areas but equilibrium in rural areas.